المعجزة القرآنية في فكر الجابري: دراسة تحليلية - جمال الدين عبد العزيز شريف (International Institute of Islamic Thought, 2011)
يتناول هذا البحث تحليلاً نقدياً لفكر محمد عابد الجابري من خلال دراسته لـ"المعجزات القرآنية"؛ وهي المعجزات التي وقعت لتدل على صدق  rفي نبوته؛ نحو معجزة "القرآن" ومعجزاته الحسية التي ذكرها القرآن؛ وهي المعجزات التي تناولها الجابري دون سواها من المعجزات التي جاءت في السنة. يتكون البحث من قسمين: تناول الأول فكر الجابري حول اعتبار القرآن معجزة للنبي؛ إذ يقر بالإعجاز اللفظي "الصوتي" للقرآن دون سواه من أنواع الإعجاز الأخرى المتعلّقة بالمعاني؛ لكنه ينكر دلالة أمية النبي على الإعجاز. وتناول القسم الثاني معجزاتr  الحسية التي ذُكرت في القرآن كانشقاق القمر والإسراء والمعراج، فرأي أن هذه المعجزات الحسية هي أحداث طبيعية غير خارقة للعادة وغير مخالفة للقوانين الكونية. This paper critically analyzes the thought of Muhammad Abid al-Jabiri in his study of the miracles of Prophet Muhammad (pbuh); i.e, the miracle of Qur'an and sensory miracles mentioned in the Qur'an. The study has two sections: the first deals with the Qur'an as Prophet Muhammad's miracle that validates his Prophethood, which al-Jabiri endorses as 'phonic' or 'verbal' miracle, while disregarding other miracles related to meanings, thereby denying the indication of the Prophet's illiteracy. The second section discusses sensory miracles that are mentioned in the Qur'an, such as the eclipse of the moon and Al Isra wa Al Mi'raj (The Night Journey and Ascension).  Al-Jabiri considers such sensory miracles as ordinary natural events that are not contrary to the cosmic laws.